A New Species of Genus Anelpistina and the Second Described Nicoletiid (Zygentoma: Insecta) Species from the Mayan Ruins of Palenque, Chiapas, Mexico. (2nd December 2012) - Espinasa, Luis; Collins, Emily; Socci, Kimberly
Abstract : Recent studies on the American nicoletiid insects ("silverfish") of the subfamily Cubacubaninae have shown that the group is more species rich than previously recognized. It has become common to find that a single locality is inhabited by more than one species of nicoletiid. In previous studies, a species from genus Squamigera had been described from the rainforest surrounding the Mayan ruins of Palenque, Chiapas, Mexico. We report here the presence of two more species of nicoletiids in the same locality and we describe here a new species of genus Anelpistina . DNA sequence data and morphology are provided to differentiate these species.